God and Worldview according to al-Attas and Wall - Usmanul Khakim; Teguh Kurniyanto; Mahendra Utama Cahya Ramadhan; Muhammad Habiburrahman; Muhammad Iksan Rahmadian (TSAQAFAH, 2020)
This article aims to elaborate the thoughts of al Attas and Thomas F Wall in understanding of God; both of which agree to consider God as a central concept (core belief) in the structure of their theory of worldview. Even so, their concept of God cannot be said to be the same, where al Attas accepts religious institutions (read; Islam) and Wall although apreciated God but rejected religion (agnostic). As a result, both worldviews have different spectrums in the all concepts included concept of reality, human beings and science; where these are rooted in the concept of God. Al Attas and Wall are contemporary philosophers who are concerned in the field of worldview theory, where al Attas presents the Islamic worldview and the Wall as a representation of the Western worldview. This article is a library research using a comparative analysis of the thoughts of two figures; besides that, contain analysis is also needed to interpret what is written in the works of the two scholars. The conclusion of this article is that al Attas' concept of God is based on revelation (khabar sadiq), while Wall builds the concept of God rationally. Al Attas came to the conclusion that God is One; all His perfect attributes exist conclusively, while Wall doubts the existence of God, so Wall  attempted to undestand God  metaphorically (God as myth).